Contaminated by war: A brief history of sea-dumping of munitions. (December 2020) - Bełdowski, Jacek; Brenner, Matthias; Lehtonen, Kari K.
Abstract: Munitions introduced to the sea during military activities, including naval combat and mine warfare represent only a fraction of military material present in seas and oceans. Huge amounts of obsolete conventional munitions and chemical munitions were dumped to the sea until 1975, when London convention put a stop of sea dumping. Such munitions are a threat for maritime workers, but also for environment. Corroding shells release toxic degradation products to sediments and bottom water, and unlike other contaminants, they cannot be reduced by land measures. Only removal of source can reduce the contamination. Much work has been done in the last decade, and mechanisms of toxicity and bioaccumulation are being recognized, as well as transport and spreading mechanisms. The full assessment of the risk associated with munitions now depends on broad application of developed techniques.